Blood Pressure Trajectory, Gait Speed, and Outcomes: The Health, Aging, and Body Composition Study. (3rd May 2016) - Odden, Michelle C.; Wu, Chenkai; Shlipak, Michael G.; Psaty, Bruce M.; Katz, Ronit; Applegate, William B.; Harris, Tamara; Newman, Anne B.; Peralta, Carmen A.; ,
Abstract: Background: The present study aimed to (i) evaluate previous observations that the association of blood pressure (BP) with outcomes varies by gait speed and (ii) evaluate the association of subsequent changes in BP and cardiovascular risk. Methods: Participants included 2, 669 adults aged 70–79 years in the Health, Aging, and Body Composition (Health ABC) study. Gait speed was dichotomized at ≥1.0 m/s over a 20-m test at baseline. BP was measured at baseline, and changes in BP over 5 years were evaluated using (i) population-based trajectory models and (ii) intraindividual mean and slope. Results: Over a mean of 10 years, there were 1, 366 deaths, 336 first myocardial infarctions, and 295 first strokes. There was a differential pattern of association between baseline systolic BP and diastolic BP and outcomes among brisk and moderate speed walkers. For example, the association between higher diastolic BP and mortality was in the protective direction for moderate speed walkers (hazard ratio = 0.75; 95% confidence interval: 0.63, 0.91) per 10 mmHg higher, whereas it was null in brisk walkers (hazard ratio = 1.05; 95% confidence interval: 0.98, 1.11), p value for interaction .01. The 5-year population-based trajectories did not add important information beyond baseline BP. Individual slopes in both systolic BP and diastolic BP did not appear to have important associations with the outcomes. Conclusions: In this study, we found that the overall level of BP was associated with myocardial infarction, stroke, and death, and this association differed by baseline gait speed, whereas changes in BP were not associated with these outcomes.